Numerical Modeling of the Influence of Solar Activity on the Global Circulation in the Earth’s Mesosphere and Lower Thermosphere - Igor Mingalev; Victor Mingalev (International Journal of Geophysics)
The nonhydrostatic model of the global neutral wind system of the earth’s atmosphere, developed earlier in the Polar Geophysical Institute, is utilized to investigate how solar activity affects the formation of the large-scale global circulation of the mesosphere and lower thermosphere. The peculiarity of the utilized model consists in that the internal energy equation for the neutral gas is not solved in the model calculations. Instead, the global temperature field is assumed to be a given distribution, that is, the input parameter of the model. Moreover, in the model calculations, not only the horizontal components but also the vertical component of the neutral wind velocity is obtained by means of a numerical solution of a generalized Navier-Stokes equation for compressible gas, so the hydrostatic equation is not applied. The simulation results indicate that solar activity ought to influence considerably on the formation of global neutral wind system in the mesosphere and lower thermosphere. The influence is conditioned by the vertical transport of air from the lower thermosphere to the mesosphere and stratosphere. This transport may be rather different under distinct solar activity conditions.